Relation of happiness, hope and affection with quality of life in patients with heart failure - Nave Leal, Elisabete (2012)
Introduction: Meeting the actual role of positive psychology, begins to be recognized the relation of positive variables with health. Objective: To know the relation of happiness, hope and affection with quality of life in individuals with heart failure. Population and Methodology: 128 individuals with heart failure, 98 men and 30 women, 61.9±12,1 years of age, 6,6±3,9 years in school and 74,2% retired because of this disease. 56,3% were in Class III of New York Heart Association, with poor left ventricular ejection fraction (25,3±6,2%). The clinical history was of 9,4±8,5 years for this heart disease and had at least one hospitalization due to heart failure with 51,6% having ischemic heart disease.